An examination of sport watching behaviours of students at Universiti Putra Malaysia - Popa, Arporn; Yusof, Aminuddin (IDOSI Publications, 2011)
The purpose of this study was to investigate sport watching behaviours of students at Universiti Putra Malaysia and to determine differences in sport watching behaviours in terms of gender and nationalities. Data was collected from 259 students using survey questionnaires which were developed based on Capella’s (2001) Fan Behavior Questionnaire. Independent-samples t-tests revealed that male and female students had a significant difference in terms of sport watching behaviors in all dimensions: positive behaviors (t = 3.308, p < 0.05), negative behaviors (t = 4.104, p < 0.05) and emotionality (t = 5.383, p < 0.05). The results also showed a significant difference between local and international students in terms of positive behaviors dimension (t = 2.203, p < 0.05), but there was no significant difference in the dimensions of negative behaviors and emotionality. The results of the study were discussed in light of earlier findings concerning spectator and watching sporting event behaviors.